COVID-19 Pandemic: Opportunity to Accelerate e-Health in Indonesia - Nyoman Sutarsa; Putu Ayu Swandewi Astuti; Melinda Choy; Malcolm Moore (Universitas Udayana, 2020)
The COVID-19 pandemic has catalysed the transformation of health care provision across the globe, including Indonesia. However, adopting and implementing e-health technologies in health care system has to be done gradually with careful planning and assessment to minimise negative consequences and to ensure equity. Strategies are required to address availability of basic infrastructure, broadband internet access, health system preparedness and acceptability from the community and health professionals. Promoting e-health also means transforming the overall landscape of health systems and the societal culture around health-seeking behaviour. It will not happen overnight, it takes time and substantial investment; but the process has to start now to leverage the ‘magic’ momentum presented by the COVID-19 pandemic.